Studi Kasus Tradisi Perjanjian Toguh Romah Desa Batorasang: Analisis Hukum Islam dan Hukum Positif - Sukron; Moh. Hilal; Jezeri (Indonesian Journal of Humanities and Social Sciences, 2023)
This research will discuss the traditions of the Toguh Roman covenant as a pre-marital condition in the village of Batorasang. Prior to the marriage, the prospective husband is asked to be prepared to settle in the house of his wife, as one of the translated oral pre-marriage agreements (Law Living) in the village of Batorasang. The aim of this study is to answer: first, what is meant by an alliance agreement in Islamic law and positive, and second, how the practice of the village of Batorasang is seen from the point of view of the law and the law of Islam. The research methods used by the authors are normative-empirical with analytical descriptive properties through case and legislative approaches. (Statute Approach). As for the results of the research, they indicate that all these rules are not recognized and understood by the public because of the custom of the public in the implementation of the partnership agreement, which is only oral without the presence of written consent. Even more rarely, the agreement is not based on the wisdom of the prospective partner and only tends to the usual habit of adjustment. This is not in accordance with the law and the provisions of article 29, paragraph 1, of Act No. 1 of 1974 on Marriage.